Mesenchymal Stem Cell Therapy Facilitates Donor Lung Preservation by Reducing Oxidative Damage during Ischemia - Natalia Pacienza; Diego Santa-Cruz; Ricardo Malvicini; Oscar Robledo; Gastón Lemus-Larralde; Alejandro Bertolotti; Martín Marcos; Gustavo Yannarelli (Stem Cells International)
Lung transplantation is a lifesaving therapy for people living with severe, life-threatening lung disease. The high mortality rate among patients awaiting transplantation is mainly due to the low percentage of lungs that are deemed acceptable for implantation. Thus, the current shortage of lung donors may be significantly reduced by implementing different therapeutic strategies which facilitate both organ preservation and recovery. Here, we studied whether the anti-inflammatory effect of human umbilical cord-derived mesenchymal stem cells (HUCPVCs) increases lung availability by improving organ preservation. We developed a lung preservation rat model that mimics the different stages by which donor organs must undergo before implantation. The therapeutic schema was as follows: cardiac arrest, warm ischemia (2 h at room temperature), cold ischemia (1.5 h at 4°C, with Perfadex), and normothermic lung perfusion with ventilation (Steen solution, 1 h). After 1 h of warm ischemia, HUCPVCs (1×106 cells) or vehicle was infused via the pulmonary artery. Physiologic data (pressure-volume curves) were acquired right after the cardiac arrest and at the end of the perfusion. Interestingly, although lung edema did not change among groups, lung compliance dropped to 34% in the HUCPVC-treated group, while the vehicle group showed a stronger reduction (69%, p<0.0001). Histologic assessment demonstrated less overall inflammation in the HUCPVC-treated lungs. In addition, MPO activity, a neutrophil marker, was reduced by 41% compared with vehicle (p<0.01). MSC therapy significantly decreased tissue oxidative damage by controlling reactive oxygen species production. Accordingly, catalase and superoxide dismutase enzyme activities remained at baseline levels. In conclusion, these results demonstrate that the anti-inflammatory effect of MSCs protects donor lungs against ischemic injury and postulates MSC therapy as a novel tool for organ preservation.